Balancing Equality for the Post-War Woman: Demobilising Canada's Women Workers After World War Two - Stephen, Jennifer A. (Atlantis)

(untitled) (Mount Saint Vincent University, 2007)
Canadian federal officials assumed women would be uninterested in paid work after World War Two. "I want to get a post-war job," while a familiar refrain, found little accommodation in the post-war regime of the Canadian welfare state. Instead, government officials, women and men alike, carefully balanced liberal rights discourses alongside the priority of female domesticity.